Landscapes of care in Mexico City: Experiences, mobility, and infrastructures - Paula Soto-Villagrán (Íconos)
This article analyzes the relationships between mobility, care, and gender through the concept of “landscapes of care”. To this end, the theoretical contributions of feminist geographies of care and the theoretical tradition of the social construction of the landscape are taken up. The objective of the article is to understand the spatial-temporal dimensions that make up such landscapes and their impact on women’s urban lives. The methodological strategy is mixed, as it puts in dialogue qualitative and quantitative research techniques, a mobility survey, and mobile ethnographies with women in their daily movements. The study context was three Modal Transfer Centers in Mexico City. The main conclusions show how caregiving practices can be present in the daily journeys of women living in the Mexican capital and that transportation territories and infrastructures can be understood as spaces for caregiving that shape the experiences of caregiving on the move. In this sense, investigating landscapes of care entails making visible realities that otherwise go unnoticed, as these landscapes are present in daily journeys – principally of women – through the city, though other inhabitants may not be aware of them or observe them directly.